DEVELOPMENT OF ENGLISH READING MATERIALS TO IMPROVE READING COMPREHENSION FOR GRADE ELEVEN STUDENTS AT SMAN 2 RANTAU SELATAN - Siregar, Fatimah; Lestari, Rizki; Rusli, Muhammad (JOURNAL OF LANGUAGE, 2025)
This study aimed to develop effective English reading materials to enhance the reading comprehension skills of Grade XI students at SMAN 2 Rantau Selatan. Using the ADDIE model—comprising the stages of Analysis, Design, Development, Implementation, and Evaluation—the research employed classroom observation, interviews, expert validation, and pretest-posttest evaluations. Findings from the initial analysis indicated that students struggled to understand reading texts due to the lack of contextual relevance, unattractive content, and materials that did not match their interests or proficiency levels. The newly developed materials, focused on narrative texts and enriched with visual and culturally relevant elements, underwent validation by subject matter and media experts, resulting in validity scores of 90% and 85%, respectively. Effectiveness testing revealed a substantial improvement in student performance, with the average score rising from 58 (pretest) to 84 (posttest), and 93% of students achieving mastery. These results suggest that the developed materials are both valid and effective for use in senior high school English instruction.